2011
DOI: 10.2337/dc10-1604
|View full text |Cite
|
Sign up to set email alerts
|

Elevation of 1-Hour Plasma Glucose During Oral Glucose Tolerance Testing Is Associated With Worse Pulmonary Function in Cystic Fibrosis

Abstract: OBJECTIVECystic fibrosis (CF)-related diabetes (CFRD) is associated with declining pulmonary function and increased mortality. During oral glucose tolerance testing (OGTT), CFRD is defined by 2-h plasma glucose (PG2). We hypothesized PG elevations during OGTT resolving by 2 h, not meeting CFRD criteria, influence pulmonary function in CF. Thus we investigated the frequency of elevated 1-h OGTT PG (PG1) and its relationship with pulmonary function.RESEARCH DESIGN AND METHODSRetrospective review of OGTTs was per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0
6

Year Published

2012
2012
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 125 publications
(101 citation statements)
references
References 15 publications
2
93
0
6
Order By: Relevance
“…This can be explained by the parallel decrease in weight as well as height scores. Previous studies have related the development of CFRD to deterioration in lung function [23][24][25]. This relation is confirmed by our results.…”
Section: Discussionsupporting
confidence: 82%
“…This can be explained by the parallel decrease in weight as well as height scores. Previous studies have related the development of CFRD to deterioration in lung function [23][24][25]. This relation is confirmed by our results.…”
Section: Discussionsupporting
confidence: 82%
“…We have previously shown that bronchiolitis obliterans syndrome is the main cause of death after LTx, irrespective of DM status (8). DM may directly impair lung function in LTRs, as it does in the general population (30,31), and in patients with CF (32,33). Supporting a lung-related mechanism of mortality are the ISHLT reports of donor DM conferring a significantly increased risk of 1-year mortality (2,34), since lungs from donors with DM may already have changes predisposing to graft dysfunction or fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Brodsky et al 99 carried out OGTTs in 101 patients and found that isolated 1-hour hyperglycaemia (i.e. with normal 2-hour levels) was associated with reduced FEV 1 , although numbers were few, with only nine patients in this group.…”
mentioning
confidence: 99%